Factors affecting employee performance in regionally owned enterprises in Indonesia - Handoyo, Sigit; Purwitasari, Heppy Yuniartha; Utami, Endah (International Journal of Innovative Research and Scientific Studies, 2025)
This article analyzes the factors that can influence employee performance at Regional Owned Enterprises (ROE), Klaten Regency, Indonesia. The factors tested in this research are the influence of religiosity, organizational culture, internal control, discipline, and incentives on employee performance. This research focuses on all active employees at Klaten Regency Regional Owned Enterprises (ROE). The sample in this study consisted of 110 respondents from various departments and various types of employees and was analyzed using the Partial Least Squares (PLS) program. The results of this research indicate that the religiosity and incentive variables have no impact on employee performance. It can be said that the influence of religiosity will not be able to improve employee performance, and this research found that the problem of religiosity is a personal problem that is not related to work. Meanwhile, incentives are not able to boost employee performance because employees feel satisfied with what they have received. The variables of organizational culture, internal control and discipline, will significantly improve employee performance. So, this research provides implications regarding the importance of emphasizing a good organizational culture by management for all members of the organization as well as continuing to implement a good internal control system and not ignoring employee work discipline.